Search for neutral Higgs boson production through the process e+e- → Z* Hº - Dova, María Teresa (1996)
The results of the searches for neutral Higgs boson production in the process e+e- --+ Z* Ho are reported, focusing on Higgs boson masses below 70 GeV. The data sample consists of three million hadronic Z” decays collected by the L3 experiment at LEP from 1991 through 1994. No signal is found leading to a lower limit on the mass of the Standard Model Higgs boson of 60.2 GeV at 95% C.L. These results are also interpreted in the framework of the General Two Doublet Model and limits on the nonstandard Higgs boson production through the process e + e - 4 Z* ho are set. A lower limit of 66.7 GeV at 95% CL. is obtained for the case where the Higgs decays into an invisible final state.